Palaksanaan UKS ( Implementasi Program Adiwiyata) di SDN 03 Alai Kota Padang - Septi Damai Yanti; Syahril Syahril; Anisah Anisah; Rifma Rifma (Journal of Educational Administration and Leadership, 2022)
This study cannot see the implementation of UKS seen from the implementation of the SDN 03 Padang City program, which includes 4 environmental factors, environmental regulations, participatory-based environmental activities, and management of environmental supporting facilities. This case study uses a descriptive qualitative approach. The key information in this study is the homeroom teacher of class 1 as one of the Adiwiyata team at SDN 03 Alai, Padang City. Using data methods through observation, interviews, and documentation studies. From the research conducted at SDN 03 Alai, Padang city in July-September, the conclusion was that the implementation of UKS in terms of the implementation of the Adiwiyata program at SDN 03 Alai, Padang City was going well. Judging by the 4 adiwiyata components (1) the development of an environmentally friendly school with the school updating its vision and mission that contains environmental values ​​and has set the budget in the RKAS for the Adiwiyata program in the framework of protecting and managing the school environment. (2) Development of an environment-based curriculum by integrating environmental knowledge materials in both extracurricular subjects and activities. (3) Development of participatory based activities involving environmental agendas held by schools or outside parties. (4) The development and management of environmental supporting facilities can be seen from the use of greenhouses and pharmacies as learning media. The school's efforts to foster student participation in the Adiwiyata program have carried out various activities held by the school or organized by parties outside the school and conducted seminars or workshops